New Mike's Auto Repair Shop a feasibility study Danio Z. Arceo, alvar A. Barbo, Mari Toni C. Barbo, Augusto P. Borra, Mike I. Chin, Jr., Virgilio Rey Dureza, Arnulfo G. Suganob. - Arceo, Danilo Z.; Barbo, Alvar A.; Borra, Augusto P.; Chin, Mike I., Jr.; Dureza, Virgilio Rey.; Suganob, Arnulfo G.; Barbo, Mari Toni C. (1997)
Executive summary -A. Description of the Proponent : Name of the the firm (D' ABC & S Corporation ; Location of Plant and Office (New Mike's Auto Repair Shop, Brgy. San Rafael, Mandurriao, Iloilo City (near Diversion Road).Brief history of the project : The proliferation of motor-driven vehicles, necessitates the need for mechanics to maintain them also increases. With the filipino culture of keeping cars running and serving the owner until it is practically torn to pieces, more and more cars need servicing. at first only the constantly moving parts need maintenance. Later body works, or the replacement of corroded and dented portions have to be done. Later still, upholstery and reclining also came into the scene. All these created an ever-increasing need of mechanics and experts in the repair and maintenance of cars. Yet this scenario takes place only for the usual wear-and-tear portions out of normal use. As more cars get on the road, accidents occur rendering vehicles unfit for use until the damaged portions are fixed, further increasing the need for repair services. With this, entrepreneurial opportunities comes out, one such venture is MIKE's AUTO REPAIR SHOP located near the Iloilo Supermart in Molo district, Iloilo City. Operated by one of the incorporators of D'ABC & S Corp., it was established in the 60's by Mike Sr.. However, upon his death, this was taken over by his son, Mike Jr. As automotive repair business became profitable, other firms also set up their own repair shops, some even equipped with modern technology to cut down on labor cost and time of several processes. For many Filipinos who consider their cars as extensions of their homes, they cannot find satisfaction unless they see that a shop is also well-equipped and the personnel experienced in their line of work. Thus several small and medium-sized shops, in response to the challenges put up by these well-capitalized competitors, put up a Cooperative called the Iloilo Metalcrafts and Auto Builders' Association, of which MIKE'S AUTO REPAIR SHOP IS A MEMBER. Yet cutting costs alone as brought about by the membership to the Cooperative is only an aspect in the lucrative business. A repair shop also needs to upgrade on the vailable technology to make work more precise and faster. However, acquiring new technology requires large amount of investment which fir most entrepreneurs in the city is hard to cope up with. So, the proprietor of the shop, approached his close friends and offered co-proprietorship (as stockholders) in the planned upgrading, and modernization of the shop. His plans were eagerly accepted and D' ABC & S Corp. was established. D' ABC & S is a corporation established to undertake automotive repair and maintenance as its main line of business. It is composed of MMBM graduates of university of the Philippines in the Visayas Graduate Program. Its Board of Directors are as follows: Board of Directors-Danilo Z. Arceo (Chairman), Mike I. Chin, Jr. (Vice-Chairman), Maritoni C. Barbo (Secretary), Augusto P. Borra (Treasurer), Alvar A. Barbo (Member), Rey Virgilio Dureza (Member), Arnulfo G. Suganob (Member). B. Brief description of the project : The New MIKE'S AUTO REPAIR SHOP will provide quality but reasonably-priced car repair and maintenance service car repairs in the City of Iloilo rivalling those of the car dealers themselves. Two types of repair service will be the main business of the New MIKE'S AUTO REPAIR SHOP. The first is the regular repairs due to the normal wear-and-tear of the different parts of vehicles. The second type and the more profitable one is the repair of accident-related damages. The latter are generally paid for by insurance companies, hence, payment is generally assured. Fabrication or assembly of vehicles from second-hand and brand-new parts (in local parlance "pasad") would be a minor form of operations and its contribution to the total revenue of the firm is expected to be minimal as compared to the first two activities. The shop will offer quality service aided by modern equipment to minimize the breakdown time of vehicles which cause anxiety to the owners. However, the planned pricing, will be lower than other shops, especially the "casa" or dealers' repair service pricing. It will be easily accessible and strategically located at the center of several districts comprising the City of Iloilo-Jaro to the North, Mandurriao to the West, Villa and Molo to the south, The City Proper to the East and Lapaz in the northeast. C. Highlights of the feasibility study-1) Market aspect- the market study indicates the following conclusions: the market for automotive repair in the city is already established. While there are several repair shops in the city, only a few and tear as well as to natural causes or may be out of an accident. There is a monthly average of 420 to 560 losses claimed against insurance companies involving vehicles insured with them. major competitors which are accredited by these insurance companies can accommodate around 56% or 282 repairs only per month. The 60 units of repair done monthly with only half coming from insurance company paid repairs represents only a 6% portion of the accident-related repairs, leaving 38% still unfilled. However only half of the repairs to be undertaken by the New Mike's Auto shop Repair Shop is accident-related. Out of more than a hundred thousand vehicles in the street and an annual increase of over 5,000 units, even if only 1/2 of 1% of these would be needing repair, this is over 5,000 a year. Definitely, there is enough room in the market where the New Mike's Auto Repair Shop can fit in without creating a sizeable change in the whole market. 2) Technical aspect - The technical study shows that: The processes to be employed by the New MIKE'S AUTO REPAIR SHOP are technically common and financially feasible. Only 3 units of equipment are to be purchased from Manila (which includes technical support) while the rest are either available in local hardware stores or from the existing MIKE'S AUTO REPAIR SHOP which will be turned over by the former owner as his contribution to the new corporation. There are readily available direct materials and supplies at reasonable prices in a metalcrafts cooperative and various automotive and hardware stores in the city. There are available graduates from the different universities and colleges as well technical schools in the city which can provide the necessary personnel required by the shop. Workers are also available out of the rolls maintained by the Iloilo Metalcrafts and Auto Builders Association. The compensation and benefits to be given are comparable or even higher in some instances when compared to other establishments in the industry and at the same time provide comfortable margin to the firm. 3) Management Aspect - The Board of directors have sufficient background in running, a business and one has years of experience on this type of business. Other members, however, are relatively new in this field. As noted above, the required personnel to fill up administrative and operations positions are readily available. The corporate structure was chose for its long life and ease of accumulating the initial capital. 4) Financial Aspect - The financial study indicates that: Income and cash flows are expected to be positive during the five-year period under study. However, there is aa need to resort to revolving credit line especially during the first two years of operations to provide the necessary buffer at times when cash flow is tight. The New MIKE'SS AUTO REPAIR SHOP would have a high level of short-term and long-term solvency during the said period. Current ratio is expected to be maintained at least 3:1 except at the time when the lot it is using is pad for. Debt in most instances would constitute 16% to 20% f total capitalization, except during the first year of operations. During the first two years however, return on owners' equity would not be below 20% and is expected to shoot up to around 70% on the fifth year. Generally, assets are expected to generate revenue of 6.48 times in a year during the first but declining steadily to 2.65 time on the fifth due to the acquisition of additional properties. D.) Project Timetable - Upon the agreement of the incorporators and the contribution of the initial capitalization required, the following schedule of activities are to be followed to facilitate the early operations of the proposed project. 1. Occupation of the Project Site - October 1997 ; 2. Construction of Necessary Structure -October 15 - December 15, 1997 ; 3. Acquisition of Machinery and Equipment - December 1997 ; 4. Hiring of Personnel - December 1997 ; 5. Approximate Date of Operations - January 1998. E.) Social desirability - The project is socially desirable for various reasons. Its service is expected to revive vehicles damaged out of normal use or from accidents. Otherwise, these could have landed in a junk shop and add to the mounting wastes, which is already a global phenomenon. On the average, it can provide direct employment to at least 25 employees and workers annually. It can further provide employment to other related businesses such as upholstery shops, aircon repair shops, oil and lubricants dealers, etc. The taxes and other fees expected to be paid to the government will be from â‚±1.2 million on the first year to â‚±5.8 million in the fifth year--enough to pay for a year's personnel expenses of a small government office. It will also put into socially beneficial activities the knowledge learned by some of the graduates of the Master of management program of the University of the Philippines in the Visayas.
Feasibility Study (BM 238) -- Iloilo City : UPV : CM, June 141997